Intrusive luxation in a child – a four-year follow-up (Research, Society and Development, 2022)
Dental trauma in children mainly results from general falls, favored by the lower resilience of the alveolar bone due to its higher porosity. Intrusive luxation is the tooth dislocation into its alveolus, in an axial direction. Clinically, this type of trauma may present in different severities: Grade I (mild partial intrusion, in which more than 50% of the crown is visible), Grade II (moderate partial intrusion, where less than 50% of the crown is visible), Grade III (severe or complete intrusion of the crown). This study reports a case of intrusive luxation in a child, as well as discusses diagnosis, therapeutic modalities, and follow-up of the case. A 15-month-old patient, attended the Baby Clinic of the Faculty of Dentistry of Araçatuba  one week after suffering a trauma that resulted in total intrusion of tooth 51. Clinical examination revealed swollen gums in addition to the absence of tooth 51. After X-ray examination, total intrusion of tooth 51 was confirmed, with the apex of the root displaced in the buccal direction. The treatment strategy adopted was the spontaneous re-eruption of the tooth; in addition, the child was instructed on occlusal relief (control of the use of pacifiers and baby bottle, and habits such as onychophagy), and regarding oral hygiene. After three months follow-up, total eruption of tooth 51 was observed, and gums and apex of the traumatized tooth presented normal aspects. It can be concluded that clinical and radiographic control, especially in cases of traumatic injuries in primary dentition, in addition to monitoring until the eruption of the permanent teeth to detect possible sequelae in successor teeth can be presented as efficient alternatives for the treatment of intrusive luxation in teeth with incomplete rhizogenesis.